Philosophy in engineering education - Nataliya V. Popkova (Moscow Polytechnic University, 2022)
In the article the position of philosophy as the subject intended for obligatory studying by the future technical experts is considered. Merits and demerits of a philosophical discourse for dominating technical rationality are shown. The leading role of philosophy in construction of a new, not-technogenic and more humane society is defined.